Test method for performance of highland barley fiber ecological concrete

By modifying barley fibers and applying them in ecological concrete, the damage to the ecosystems of traditional slope protection materials in Tibet has been solved, and the mechanical properties and freezing resistance of concrete have been significantly improved, providing more suitable slope protection materials for high-altitude and high-altitude areas.

CN114965032BActive Publication Date: 2025-04-11NORTH CHINA UNIV OF WATER RESOURCES & ELECTRIC POWER +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210035944.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-13
Publication Date
2025-04-11
Estimated Expiration
2042-01-13

AI Technical Summary

Technical Problem

In high-altitude and high-altitude areas in Tibet, traditional slope protection materials cause damage to the ecosystem, and the existing technology is difficult to effectively test the performance of highland barley fiber ecological concrete.

Method used

The ecological concrete performance testing method of barley fiber is adopted, including the modification treatment of barley fiber, the determination of dosage, the mechanical performance test and the freezing resistance test. The modification treatment involves soaking and drying in a mixed solution of glacial acetic acid and NaClO2 at 50°C, and the doping amount is comprehensively analyzed by low doping amount and high doping amount.

Benefits of technology

Through the application of modified barley fibers in ecological concrete, the mechanical properties and frost resistance of concrete are significantly improved, and can be widely promoted and applied in high-altitude areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114965032B_ABST
    Figure CN114965032B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for testing the performance of highland barley fiber ecological concrete, comprising the following steps: (1) modifying highland barley fiber; (2) determining the amount of highland barley fiber added; (3) testing the mechanical properties of highland barley fiber concrete; (4) testing the antifreeze performance of highland barley fiber concrete; and (5) antifreeze results and analysis of highland barley fiber ecological concrete. By testing the performance of highland barley fiber ecological concrete, the present invention can conclude that adding modified highland barley fiber to ecological concrete greatly enhances the antifreeze effect of the mechanical properties of concrete, and can be widely promoted and applied in the Qinghai-Tibet Plateau.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete testing, and in particular relates to a method for testing the performance of highland barley fiber ecological concrete. Background Art

[0002] Tibet is located in the Qinghai-Tibet Plateau, with an average altitude of more than 4,000 meters. The climate is cold and dry, with a large temperature difference between day and night. The ecological self-regulation ability is fragile. If traditional slope protection materials such as mortar masonry, dry masonry, and ordinary concrete are used, it will damage the local ecosystem and lead to a sharp decline in biodiversity. In contrast, the application of ecological concrete to slope protection in high-altitude and cold areas can not only solve the problem of bank protection and anti-scouring, but also green the slopes and reduce the heat island effect. It perfectly combines the hardening of concrete with greening, making concrete and natural ecology coexist harmoniously.

[0003] Based on the natural conditions in Tibet, this paper studies the performance of ecological concrete in high-cold and high-altitude areas and its application in slope protection projects. The so-called ecological concrete is a new type of material with performance between ordinary concrete and cultivated soil. It uses large-size coarse aggregate as the skeleton, cement paste and admixtures to form a concrete structure with honeycomb pores, which is breathable and water-permeable.

[0004] Highland barley fiber is produced in the Ali region of Tibet. Highland barley fiber is brownish yellow, with a diameter of 100-500μm, a length of 20-80cm, a density of 1.12g / m³, and a circular cross section. Highland barley fiber has the characteristics of being slender, which determines that it can play a role in toughening concrete. Therefore, adding highland barley fiber to ecological concrete is a way to improve the toughness of concrete. Before specific implementation, the performance of highland barley fiber ecological concrete needs to be tested. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for testing the performance of highland barley fiber ecological concrete.

[0006] In order to solve the above technical problems, the present invention adopts the following technical scheme: a method for testing the performance of highland barley fiber ecological concrete, comprising the following steps:

[0007] (1) Modification of highland barley fiber;

[0008] (2) Determination of the amount of highland barley fiber added;

[0009] (3) Mechanical properties test of highland barley fiber concrete;

[0010] (4) Test on the frost resistance of highland barley fiber concrete;

[0011] (5) Results and analysis of frost resistance of highland barley fiber ecological concrete.

[0012] The specific process of step (1) is: soaking the highland barley fiber in a mixed solution of 3% glacial acetic acid and 1.5% NaClO2 at 50°C for 4 hours, and then drying it in an oven at a temperature of 80°C.

[0013] In step (2), the dosage of highland barley fiber is divided into high dosage and low dosage. The low dosage of highland barley fiber concrete has obvious improvement in crack resistance, while when a large amount of highland barley fiber is added to concrete, it mainly affects the compressive strength of concrete. Design 1Kg / m 3 , 2Kg / m 3 , 3Kg / m 3 , 4Kg / m 3 , 5Kg / m 3 Five different highland barley fiber dosages were used to comprehensively analyze the mechanical properties of highland barley fiber concrete and select the optimal dosage.

[0014] The specific process of step (3) is as follows:

[0015] ① The highland barley fiber after modification in step (1) is subjected to X-ray diffraction analysis and scanning electron microscopy analysis to study the microscopic mechanism of fiber modification;

[0016] ②Using a single factor test, different amounts of highland barley fiber were added to concrete according to the change in quantity. The concrete water-cement ratio was 0.3 and the porosity was 25%. After mixing, the mold was filled and the filled mold was placed in a cool place to avoid water evaporation. After 24 hours, when the concrete test block had a certain strength, the concrete test block was taken out of the mold, and then the concrete test block was moved to a more stable and constant humidity curing room for curing. After 28 days, it was taken out and the mechanical properties of highland barley fiber concrete were measured with a Hualong mechanical properties testing machine. The mechanical properties include compressive strength, splitting strength and flexural strength.

[0017] ③ Organize and plot the mechanical properties data of highland barley fiber concrete obtained in step ②, and by analyzing the images and data, obtain the improvement of the mechanical properties of concrete by highland barley fiber; import 5 groups of mechanical properties data of highland barley fiber concrete with different dosages into the software Origin, and after drawing and analyzing, it can be obtained how the mechanical properties of concrete change with different highland barley fiber dosages.

[0018] The specific process of step (4) is as follows:

[0019] A) Take out the concrete test block cured in the curing room and observe the regularity of its surface. Then soak the concrete test block in room temperature water for at least 4 days and then take it out. After wiping off the residual water on the surface of the concrete test block, weigh the mass of the concrete to obtain the initial mass of the concrete.

[0020] B) First, set the freeze-thaw box control panel, set the temperature between -15℃ and -20℃, and the temperature should always be controlled within the range of no more than 15℃, set three freeze-thaw cycle gradients, 20 times, 40 times, and 50 times respectively; according to the different content of highland barley fiber, add 1Kg / m 3 , 2Kg / m 3 , 3Kg / m 3 , 4Kg / m 3 , 5Kg / m 3 Five groups of highland barley fiber concrete test blocks with different dosages were placed in a freeze-thaw box;

[0021] C) When the test reaches 20 freeze-thaw cycles, stop the freeze-thaw box and wait for the concrete test blocks to be completely thawed. Then take out one-third of the concrete test blocks, weigh the mass of the concrete test blocks, and then measure the compressive strength of the concrete test blocks. After the test is completed, set 20 cycles to continue running the freeze-thaw box. After the operation is completed, take out the required concrete test blocks, weigh them and measure their compressive strength, and then continue to set 10 cycles. After the cycle is completed, measure the weight and compressive strength; if the mass of the concrete test block is reduced to less than 95% of the original after a certain cycle, or the compressive strength is reduced to less than 75% of the original, the concrete test block is considered to be damaged, the experiment is over, and the concrete anti-freeze grade is recorded as D + the number of freeze-thaw cycles.

[0022] Step (5) includes antifreeze data processing, appearance analysis, mass loss rate analysis and compressive strength loss rate analysis.

[0023] By adopting the above technical scheme, the present invention first modifies highland barley fiber, adds the treated highland barley fiber into ecological concrete, conducts mechanical property test and antifreeze property test on the performance of highland barley fiber concrete, and analyzes the test results. The final conclusion is:

[0024] 1. Highland barley fiber is bonded with cement paste in concrete, so that the gravel, cement paste and highland barley fiber in concrete are bonded to each other to form a strong network. Such a network structure makes the external impact force fully dispersed, the deformation resistance of concrete is improved, and the mechanical properties are greatly improved; however, when the proportion of highland barley fiber in concrete is too high, the specific surface area of ​​the fiber increases, and the increase in fiber makes the highland barley fiber absorb a lot of water when mixing concrete. The water-saturated highland barley fiber is difficult to combine with cement paste, and the number of highland barley fibers wrapped in cement paste in concrete decreases rapidly. If the proportion of highland barley fiber in concrete continues to increase, the highland barley fiber will absorb a lot of water, resulting in the cement paste and highland barley fiber being completely disconnected, the concrete density decreases rapidly, and the concrete skeleton will also collapse completely, so the mechanical strength of concrete also decreases dramatically.

[0025] 2. The presence of highland barley fiber improves the frost resistance of concrete.

[0026] 3. The addition of highland barley fiber in the early stage of freeze-thaw cycle has little effect on the frost resistance of concrete, while in the later stage of freeze-thaw cycle, highland barley fiber can effectively reduce the strength loss of concrete.

[0027] 4. The addition of highland barley fiber in the early stage of freeze-thaw cycle has little effect on the frost resistance of concrete, while in the later stage of freeze-thaw cycle, highland barley fiber can effectively reduce the loss of compressive strength of concrete.

[0028] In summary, by testing the performance of highland barley fiber ecological concrete, the present invention can conclude that adding modified highland barley fiber to ecological concrete greatly enhances the antifreeze effect of the mechanical properties of concrete, and can be widely promoted and applied in the Qinghai-Tibet Plateau. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope image of highland barley fiber after pretreatment magnified 50 times;

[0030] Figure 2 This is a scanning electron microscope image of highland barley fiber after pretreatment magnified 10,000 times;

[0031] Figure 3 is the XRD image curve under different modification treatment conditions;

[0032] Figure 4 This is a scanning electron microscope image of the modified highland barley fiber magnified 50 times;

[0033] Figure 5 This is a scanning electron microscope image of the modified highland barley fiber magnified 10,000 times;

[0034] Figure 6 is a schematic diagram of thermogravimetric image analysis of unmodified highland barley fiber;

[0035] Figure 7 This is a schematic diagram of thermogravimetric image analysis of No. 8 modified highland barley fiber;

[0036] Figure 8 This is a comparative diagram of infrared spectrum analysis of No. 0 and No. 1 modified highland barley fibers;

[0037] Fig. 9 This is a comparative diagram of infrared spectrum analysis of No. 0 and No. 6 modified highland barley fibers;

[0038] Fig.10 This is a comparative diagram of infrared spectrum analysis of No. 0 and No. 8 modified highland barley fibers;

[0039] Fig.11 This is the graph showing the change of mechanical properties of highland barley fiber concrete with fiber content;

[0040] Fig.12This is the result diagram of mass loss rate of highland barley fiber concrete;

[0041] Fig.13 This is the result graph of compressive strength loss rate of highland barley fiber concrete. DETAILED DESCRIPTION

[0042] The highland barley fiber ecological concrete performance testing method of the present invention comprises the following steps:

[0043] (1) Modification of highland barley fiber;

[0044] (2) Determination of the amount of highland barley fiber added;

[0045] (3) Mechanical properties test of highland barley fiber concrete;

[0046] (4) Test on the frost resistance of highland barley fiber concrete;

[0047] (5) Results and analysis of frost resistance of highland barley fiber ecological concrete.

[0048] The specific process of step (1) is: firstly, the highland barley fiber is washed with distilled water to remove impurities on the surface of the highland barley fiber, and then the washed highland barley fiber is dried at 80°C for 2 hours to obtain the pretreated highland barley fiber; the scanning electron microscope image of the pretreated highland barley fiber is as follows: Figure 1 (SEM image of highland barley fiber after pretreatment at 50 times magnification) and Figure 2 (Scanning electron microscope image of highland barley fiber after pretreatment, magnified 10,000 times) Figure 1 It can be seen that the surface of the untreated highland barley fiber is relatively smooth and the thickness is relatively uniform. Figure 2 It can be seen that there are only a few pits and grooves on the surface. These surface defects can make the barley fiber and concrete better combined and not easy to be pulled out, thereby improving the mechanical properties of ecological concrete.

[0049] The test reagents and test instruments used for the modification of the pretreated highland barley fiber are shown in Table 1 and Table 2 respectively:

[0050] Table 1 Test reagents

[0051]

[0052] Table 2 Test instruments

[0053]

[0054] The specific process of the modification treatment is as follows: the pretreated highland barley fiber is cut into small segments of 10 to 25 mm, and the orthogonal experimental design shown in Table 3 is carried out through three factors and three levels.

[0055] Table 3 Orthogonal factors table

[0056]

[0057] From the above orthogonal experimental design, it can be seen that there are 9 modification schemes for highland barley fiber, and the schemes for pretreatment under different conditions are shown in Table 4.

[0058] Table 4 Orthogonal test design table

[0059]

[0060] In the above experiment, 9 groups of highland barley fibers were first soaked in their respective treatment solutions at a temperature of 50°C for 2 hours, and then the treated highland barley fibers were rinsed with distilled water until the pH value of the last washing solution showed 7. Then the 9 groups of solutions were treated at different heat treatment temperatures for different times.

[0061] During the heating pretreatment process, a series of physical and chemical reactions occur in highland barley fiber, and its chemical composition will change. During the treatment process, the color of the fiber gradually turns yellow and the color of the solution gradually becomes darker.

[0062] Then the characterization method and results of highland barley fiber were analyzed. The specific process is as follows:

[0063] X-ray diffractometer is a kind of electromagnetic wave, which can penetrate a certain thickness of material. X-ray diffraction can be used to analyze and study the structure of crystals, because each material has its own unique crystal structure. When high-energy X-rays are used to irradiate the sample, the objects in the sample will be excited and the identification X-rays will be generated. The crystal surface reflection activity follows the Bragg law. The qualitative analysis of the compound can be carried out by measuring the position of the diffraction peak, and the quantitative analysis can be carried out by measuring the intensity of the diffraction peak of the spectrum. In this experiment, the X-ray diffractometer is mainly used to analyze the crystallization properties of the modified highland barley fiber after treatment.

[0064] ⒈Sample preparation

[0065] Generally speaking, samples with smaller particles, stable properties, and more uniform size distribution in a spherical shape are relatively ideal. During the sample pressing process, the entire sample slot is usually covered with powdered samples. It should be noted that if the samples are from the same series and the strength difference is large, the density of the sample is very easy to change, which may affect the diffraction intensity of the sample. In this experiment, the dried highland barley fiber was cut into sections, placed in the sample slot, and then placed in the X-ray diffractometer. The computer system connected to the X-ray diffractometer was operated to perform X-ray diffraction image analysis of the sample.

[0066] 2. Analytical methods

[0067] One of the experimental methods is the orthogonal analysis method. This experiment uses three factors, namely, treatment solution (6% NaOH, 6% NaOH + 10% H2O2, 3% glacial acetic acid + 1.5% NaClO2), treatment time (2h, 4h, 6h), and heat treatment temperature (80℃, 100℃, 120℃), to conduct orthogonal design at three levels, and then conduct XRD analysis on the modified fibers to calculate the crystallinity.

[0068] The second test method is comparative analysis, which mainly studies the effect of different treatment conditions on the crystallinity of highland barley fiber. The comparative analysis method usually compares several test data with common characteristics, so as to make certain comments and finally obtain certain experimental results. In this test, the XRD curves of highland barley fiber under treatment conditions are compared, or the XRD curves of highland barley fiber under treatment and untreated conditions are compared to analyze the crystallinity of highland barley fiber under different conditions; the morphology of highland barley fiber under different pretreatment conditions is compared to study the effect of pretreatment on fiber structure.

[0069] ⒊ XRD image analysis of highland barley fiber

[0070] The highland barley fibers were modified by the reagents No. 1-9 in Table 5. When the crystal structure of cellulose was studied by X-ray diffractometer, the crystallinity of the cellulose fibers was determined based on the intensity and position of the diffraction points.

[0071] Table 5 Fiber crystallinity index under different conditions

[0072]

[0073] Corresponding to the experimental numbers in Table 5, the XRD image curves under different modification conditions are obtained, such as Figure 3 This experiment uses the orthogonal test method to analyze the relationship between different processing conditions and crystallinity. After calculation, it can be known that the crystallinity of No. 8 is better.

[0074] 4. SEM image analysis of highland barley fiber

[0075] The scanning electron microscope uses a point-by-point imaging image decomposition method, which is converted into a video signal in sequence and proportion. After network video amplification and control signal data processing, it can be sent to the grid of the fluorescent screen where the electron beam passes synchronously through the scanning, and is used as the intensity of the electron beam of the cathode ray tube. Since the sample scanning and the SEM equipment scanning are completely synchronized, it can become an enlarged image of the sample.

[0076] Features of scanning electron microscope:

[0077] 1) The sample preparation process is simple;

[0078] 2) The degree of freedom in the sample chamber is very large;

[0079] 3) The image is three-dimensional;

[0080] 4) The magnification range is relatively large and the resolution is relatively high;

[0081] 5) The electron beam causes little damage and contamination to the sample.

[0082] In the sample preparation of scanning electron microscope, for powder samples, the powder samples are bonded to the sample holder with conductive glue (or collodion, or double-sided tape) and coated with conductive film, or the powder sample material is made into a cell suspension, which is dripped on the sample holder, and the solution is plated with conductive film after volatilization. In this experiment, highland barley fiber is bonded to the sample holder. Since highland barley fiber is a non-conductive material, carbon or gold spraying treatment is required on the surface of highland barley fiber to avoid the accumulation of charge under electron beam irradiation, which affects the image quality.

[0083] Scanning electron microscope images of modified highland barley fibers, such as Figure 4 (Scanning electron microscope image of modified highland barley fiber magnified 50 times) and Figure 5 As shown in (Scanning electron microscope image of modified highland barley fiber magnified 10,000 times), the fiber surface becomes rough and many scratches can be seen on the fiber surface. This structure is conducive to the adhesion of highland barley fiber to ecological concrete. In addition, many flocs can be seen on the fiber surface. This is because the lignin and hemicellulose of the treated highland barley fiber are removed and float on the fiber surface, leaving the cellulose fully exposed and smooth. By removing lignin and hemicellulose, the mechanical properties of highland barley fiber are improved, which is convenient for subsequent research.

[0084] ⒌ Thermogravimetric image analysis of highland barley fiber

[0085] like Figure 6 (Schematic diagram of thermogravimetric image analysis of unmodified highland barley fiber) and Figure 7 (Schematic diagram of thermogravimetric image analysis of No. 8 modified highland barley fiber), Figure 6 and Figure 7 As shown, it can be seen that at 0-200℃, the mass change in this stage is mainly the loss of water on the surface of the straw, and the DSC curve shows that it is an endothermic process. At 280-380℃, the mass reduction at this time is mainly the thermal decomposition of hemicellulose and cellulose. In this process, curve No. 0 drops sharply, and curve No. 8 drops evenly. This shows that the modification has removed part of the hemicellulose from the highland barley fiber. This part is an exothermic process. At 380-600℃, the mass reduction in this process is mainly the loss of the constituent water of the straw (the component is sugar), and only carbon is left at 600℃. The DSC curve shows that it is an exothermic process.

[0086] ⒍Infrared spectrum image analysis of highland barley fiber

[0087] For the modified highland barley fiber, the changes in the infrared spectrum images under different solution environments are compared to compare the treatment effects. Comparing the untreated sample No. 0 and the sample No. 1 treated with alkaline solution, the infrared spectrum images are as follows: Figure 8 (A comparative diagram of infrared spectrum analysis of No. 0 and No. 1 modified highland barley fibers) is shown. Figure 8 It can be seen that compared with No. 0, No. 1 has a peak of 1255.35 cm in the absorption peak of hemicellulose. -1 The CO stretching peak at 1735 cm -1 The C=O stretching peak disappears at 1600, 1514, and 1462 cm -1 The absorption peak at disappeared, indicating that the modification result of sodium hydroxide solution treatment was very good, and the removal rate of hemicellulose and lignin was high.

[0088] By comparing the infrared spectra of untreated No. 0 highland barley fiber and No. 6 highland barley fiber treated with alkaline hydrogen peroxide solution, we can get Fig. 9 (Sketch of infrared spectrum analysis comparison of No. 0 and No. 6 modified highland barley fibers), Fig. 9 It can be seen that there is no obvious change in the infrared spectrum of No. 6 highland barley fiber.

[0089] By comparing the infrared spectra of untreated No. 0 highland barley fiber and No. 8 highland barley fiber treated with sodium chlorite and glacial acetic acid solution, we can get Fig.10 (Sketch of infrared spectrum analysis comparison of No. 0 and No. 8 modified highland barley fibers), Fig.10 It can be seen that the processing results of sample No. 8 are also good, at 1600cm -1 The aromatic skeleton vibration peak at 1514 cm -1 The C=C stretching vibration peak in the aromatic ring at was removed, indicating that the lignin contained in the highland barley fiber was mainly removed after modification with No. 8.

[0090] The morphology and structure of highland barley fiber were studied under the above 9 groups of different treatment conditions. The results showed that the modification treatment can improve the crystallinity of highland barley fiber and change the appearance of highland barley fiber. Through the orthogonal experimental design method and the comparison method, the influence of different pretreatment factors on the crystallinity index of highland barley fiber was obtained, so as to find the optimal level combination.

[0091] Through the macroscopic morphology analysis of untreated fibers and the microstructural analysis of SEM, it can be concluded that the surface of untreated highland barley fibers is very smooth, and the highland barley straw is relatively hard due to the presence of cellulose, hemicellulose, lignin, etc. in the fibers.

[0092] The highland barley fiber was modified through a three-factor three-level orthogonal design experiment. From the experimental phenomena, it can be seen that under the conditions of 3% glacial acetic acid + 1.5% NaClO2 + 4h + 80℃, the color of the solution gradually turned yellow, and then the color became darker and darker, showing brown or dark brown.

[0093] Through XRD and infrared spectrum image analysis, the crystallinity index under different treatment conditions can be obtained. The results show that the crystallinity index of test group 8 is 55.55%, and its crystallinity is the best. Therefore, 3% glacial acetic acid + 1.5% NaClO2 + 4h + 80℃ is the optimal level combination.

[0094] By analyzing the morphology of the modified highland barley fiber using SEM, it can be concluded that the lignin, hemicellulose, fructose, etc. of the highland barley fiber are partially removed after treatment, and the fiber surface presents many orderly and clear grooves and pits. This structure is conducive to improving the interfacial adhesion between highland barley fiber and ecological concrete.

[0095] Thermogravimetric image analysis showed that after modification, part of the hemicellulose was removed from the highland barley fiber, so that the remaining part of the highland barley straw was mainly cellulose.

[0096] Through the above modified analysis, it can be seen that in theory, the surface modification treatment scheme No. 8 has a better effect and can be considered to be added to concrete to improve its mechanical properties and frost resistance.

[0097] Since ecological concrete is made of cement, larger-sized stones, water-reducing agent and water, after hardening, the concrete relies on the connection between cement paste and stones to ensure strength. However, due to the large particle size of the stones used in this test, there are large gaps between the stones. Once such a structure of concrete is subjected to external forces in the actual working environment, it is very easy to crack. After the cracks expand, the overall structure of the concrete will completely collapse. Therefore, adding a certain length and volume of highland barley fiber when mixing concrete can not only fill the gaps in the concrete, but also connect the highland barley fiber with the cement paste, making the entire concrete more stable and able to resist greater stress concentration, thereby improving the strength of the concrete. The amount of highland barley fiber is a critical factor.

[0098] The dosage of highland barley fiber in step (2) can be divided into high dosage and low dosage. The fiber concrete with low dosage has obvious improvement in crack resistance, while when more fiber is added to concrete, the main effect is on the compressive strength of concrete. This test design is 1Kg / m 3 , 2Kg / m 3 , 3Kg / m 3 , 4Kg / m 3 , 5Kg / m 3Five different fiber dosages are used to comprehensively analyze the mechanical properties of fiber concrete and select the optimal dosage.

[0099] Compared with the untreated No. 0, the surface of the treated No. 8 highland barley fiber appears very rough, and we can see that the surface of the treated fiber has a morphology similar to scratches, which is conducive to the adhesion of highland barley fiber to cement mortar. And we can also see that there are many floccules on the fiber surface, which is because after the acid and alkali treatment of highland barley fiber, the impurities such as lignin and hemicellulose in the highland barley fiber are removed and float on the fiber surface, leaving the cellulose fully exposed and becoming smooth and regularly arranged. After the modification treatment, such a structure improves the mechanical properties of highland barley fiber.

[0100] The specific process of step (3) is as follows:

[0101] ① The highland barley fiber after modification in step (1) is subjected to X-ray diffraction analysis and scanning electron microscopy analysis to study the microscopic mechanism of fiber modification;

[0102] ②Using a single factor test, different amounts of highland barley fiber were added to concrete according to the change in quantity. The concrete water-cement ratio was 0.3 and the porosity was 25%. After mixing, the mold was filled and the filled mold was placed in a cool place to avoid water evaporation. After 24 hours, when the concrete test block had a certain strength, the concrete test block was taken out of the mold, and then the concrete test block was moved to a more stable and constant humidity curing room for curing. After 28 days, it was taken out and the mechanical properties of highland barley fiber concrete were measured with a Hualong mechanical properties testing machine. The mechanical properties include compressive strength, splitting strength and flexural strength.

[0103] ③ Organize and plot the mechanical properties data of highland barley fiber concrete obtained in step ②, and by analyzing the images and data, obtain the improvement of the mechanical properties of concrete by highland barley fiber; import 5 groups of mechanical properties data of highland barley fiber concrete with different dosages into the software Origin, and after drawing and analyzing, it can be obtained how the mechanical properties of concrete change with different highland barley fiber dosages.

[0104] The optimal mix ratio (water-cement ratio 0.30, porosity 25%) was used to mix highland barley fiber concrete, and its mechanical properties were tested after curing for 28 days. A graph showing the change of mechanical properties of highland barley fiber concrete over 28 days with fiber content was drawn, as shown in Figure 2. Fig.11 (The mechanical properties of highland barley fiber concrete vary with fiber content).

[0105] The control group was ordinary concrete mixed with the best mix ratio No. 8 without adding highland barley fiber. Its average strength was 14.64Mpa in compressive strength, 3.01Mpa in splitting strength, and 1.36Mpa in flexural strength.

[0106] It can be seen that the compressive strength, splitting strength and flexural strength of concrete have obvious changes after adding highland barley fiber to concrete. 3 ~3Kg / m 3 When the amount of highland barley fiber added is 1 kg / m 3 ~3Kg / m 3 The changes in the content of highland barley fiber continued to increase, the compressive strength of concrete increased by 7.8%, 15.0% and 20.8% respectively, the splitting strength increased by 5.3%, 39.8% and 75% respectively, and the flexural strength increased by 22.5%, 47.8% and 63.8% respectively; however, when the content of highland barley fiber continued to increase, the mechanical properties of concrete began to decline.

[0107] Analyzing the above reasons, it may be because the ecological concrete used in this experiment is a large-pore concrete with many pores in the middle of the concrete. When the external impact force acts on the concrete, the stress concentration in the concrete will be very strong, causing the concrete structure to be damaged. When a certain amount of highland barley fiber is added to the concrete, the highland barley fiber will enter the gaps in the concrete to fill the holes in the concrete, making the internal structure of the concrete more compact.

[0108] In addition, highland barley fiber is bonded with cement paste in concrete, so that the gravel, cement paste and highland barley fiber in concrete are bonded to each other to form a strong net. Such a mesh structure makes the external impact force fully dispersed, the deformation resistance of concrete is improved, and the mechanical properties are greatly improved; however, when the proportion of highland barley fiber in concrete is too high, the specific surface area of ​​the fiber increases, and the increase in fiber makes the highland barley fiber absorb a lot of water when mixing concrete. The water-saturated highland barley fiber is difficult to combine with cement paste, and the number of highland barley fibers wrapped in cement paste in concrete decreases rapidly. If the proportion of highland barley fiber in concrete continues to increase, the highland barley fiber will absorb a lot of water, resulting in the cement paste and highland barley fiber being completely disconnected, the density of concrete decreases rapidly, and the concrete skeleton will also completely collapse, so the mechanical strength of concrete also decreases dramatically.

[0109] The specific process of step (4) is as follows:

[0110] A) Take out the concrete test block cured in the curing room and observe the regularity of its surface. Then soak the concrete test block in room temperature water for at least 4 days and then take it out. After wiping off the residual water on the surface of the concrete test block, weigh the mass of the concrete to obtain the initial mass of the concrete.

[0111] B) First, set the freeze-thaw box control panel, set the temperature between -15℃ and -20℃, and the temperature should always be controlled within the range of no more than 15℃, set three freeze-thaw cycle gradients, 20 times, 40 times, and 50 times respectively; according to the different content of highland barley fiber, add 1Kg / m 3 , 2Kg / m 3 , 3Kg / m 3 , 4Kg / m 3 , 5Kg / m 3 Five groups of highland barley fiber concrete test blocks with different dosages were placed in a freeze-thaw box;

[0112] C) When the test reaches 20 freeze-thaw cycles, stop the freeze-thaw box and wait for the concrete test blocks to be completely thawed. Then take out one-third of the concrete test blocks, weigh the mass of the concrete test blocks, and then measure the compressive strength of the concrete test blocks. After the test is completed, set 20 cycles to continue running the freeze-thaw box. After the operation is completed, take out the required concrete test blocks, weigh them and measure their compressive strength, and then continue to set 10 cycles. After the cycle is completed, measure the weight and compressive strength; if the mass of the concrete test block is reduced to less than 95% of the original after a certain cycle, or the compressive strength is reduced to less than 75% of the original, the concrete test block is considered to be damaged, the experiment is over, and the concrete anti-freeze grade is recorded as D + the number of freeze-thaw cycles.

[0113] Step (5) includes antifreeze data processing, appearance analysis, mass loss rate analysis and compressive strength loss rate analysis.

[0114] 1. Antifreeze data processing, as shown in Table 6, Table 7 and Table 8.

[0115] Table 6 Results of 20 freeze-thaw cycles

[0116]

[0117] Table 7 Results of 40 freeze-thaw cycles

[0118]

[0119] Table 8 Results of 50 freeze-thaw cycles

[0120]

[0121] 2. Appearance analysis

[0122] (a) By observing the concrete specimens treated with different freeze-thaw cycles, it was found that the stones on the surface of the concrete specimens became loose and easy to fall off after the freeze-thaw test, and there was a tendency for the surface of the concrete specimens to form engraved stripes. Some deformed holes could be seen on the concrete surface, and the above phenomenon became more and more obvious with the increase of the number of freeze-thaw cycles.

[0123] (b) The surface damage of ordinary concrete after the frost resistance test is more serious than that of highland barley fiber concrete, which indicates that the frost resistance of concrete is improved due to the presence of highland barley fiber.

[0124] 3. Mass loss rate analysis, plot the mass loss rate as follows Fig.12 (Result diagram of mass loss rate of highland barley fiber concrete):

[0125] Depend on Fig.12 The following conclusions can be found:

[0126] (1) The increase in the number of freeze-thaw cycles causes the mass of concrete to decrease continuously, and the mass loss of concrete continues to accelerate.

[0127] (2) The mass loss rate of concrete without highland barley fiber is very large, while the mass loss rate of highland barley fiber concrete is very small, which indicates that highland barley fiber slows down the mass loss of concrete, that is, highland barley fiber has a positive effect on the frost resistance of concrete.

[0128] (3) With the increase of freeze-thaw cycles, when the number of freeze-thaw cycles is less than 40, the change rate of mass loss rate of highland barley fiber concrete is not much different from that of ordinary concrete, but when the number of freeze-thaw cycles is greater than 40, the growth rate of mass loss rate of highland barley fiber concrete is much slower than that of ordinary concrete. This shows that the addition of highland barley fiber in the early stage of freeze-thaw cycle has little effect on the frost resistance of concrete, and highland barley fiber can effectively reduce the strength loss of concrete in the later stage of freeze-thaw cycle.

[0129] 4. Analysis of compressive strength loss rate: Plot the compressive strength loss rate as follows: Fig.13 (Results of compressive strength loss rate of highland barley fiber concrete) Fig.13 The following conclusions can be found:

[0130] (1) The loss rate of compressive strength of concrete is increasing.

[0131] (2) The compressive strength loss rate of ordinary concrete is much higher than that of highland barley fiber concrete, which shows that highland barley fiber can enhance the frost resistance of concrete.

[0132] (3) With the increase of freeze-thaw cycles, when the number of freeze-thaw cycles is less than 40, the change rate of compressive strength loss rate of highland barley fiber concrete is not much different from that of ordinary concrete, but when the number of freeze-thaw cycles is greater than 40, the growth rate of compressive strength loss rate of highland barley fiber concrete is much slower than that of ordinary concrete. This shows that the addition of highland barley fiber in the early stage of freeze-thaw cycle has little effect on the frost resistance of concrete, and highland barley fiber can effectively reduce the loss of compressive strength of concrete in the later stage of freeze-thaw cycle.

[0133] The above description is only a preferred embodiment of the present invention. The arrangement positions and corresponding directions of the components described in this embodiment are only for the convenience of those skilled in the art to understand the technical solution and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. The performance test method of highland barley fiber ecological concrete is characterized by: The following steps are involved: (1) Modification of highland barley fiber; (2) Determination of the amount of highland barley fiber added; (3) Mechanical properties test of highland barley fiber concrete; (4) Test on the frost resistance of highland barley fiber concrete; (5) Results and analysis of frost resistance of highland barley fiber ecological concrete; The specific process of step (1) is: first, the highland barley fiber is washed with distilled water to remove impurities on the surface of the highland barley fiber, and then the washed highland barley fiber is dried at 80°C for 2 hours to obtain pretreated highland barley fiber; then the pretreated highland barley fiber is immersed in a mixed solution of 3% glacial acetic acid and 1.5% NaClO2 at 50°C for 4 hours, and then dried in an oven at a temperature of 80°C.

2. The highland barley fiber ecological concrete performance testing method according to claim 1, characterized in that: In step (2), the dosage of highland barley fiber is divided into high dosage and low dosage. The low dosage of highland barley fiber concrete has obvious improvement in crack resistance, while when a large amount of highland barley fiber is added to concrete, it mainly affects the compressive strength of concrete. Design 1Kg / m 3 , 2Kg / m 3 , 3Kg / m 3 , 4Kg / m 3 , 5Kg / m 3 Five different highland barley fiber dosages were used to comprehensively analyze the mechanical properties of highland barley fiber concrete and select the optimal dosage.

3. The highland barley fiber ecological concrete performance testing method according to claim 2, characterized in that: The specific process of step (3) is as follows: ① The highland barley fiber after modification in step (1) is subjected to X-ray diffraction analysis and scanning electron microscopy analysis to study the microscopic mechanism of fiber modification; ②Using a single factor test, different amounts of highland barley fiber were added to concrete according to the change in quantity. The concrete water-cement ratio was 0.3 and the porosity was 25%. After mixing, the mold was filled and the filled mold was placed in a cool place to avoid water evaporation. After 24 hours, when the concrete test block had a certain strength, the concrete test block was taken out of the mold, and then the concrete test block was moved to a more stable and constant humidity curing room for curing. After 28 days, it was taken out and the mechanical properties of highland barley fiber concrete were measured with a Hualong mechanical properties testing machine. The mechanical properties include compressive strength, splitting strength and flexural strength. ③ Arrange and plot the mechanical properties data of highland barley fiber concrete obtained in step ②, and obtain the improvement of the mechanical properties of concrete by highland barley fiber by analyzing the images and data; The mechanical properties data of 5 groups of highland barley fiber concrete with different dosages were imported into the software Origin. After drawing the graphs and analyzing them, it can be found out how the mechanical properties of concrete change with different dosages of highland barley fiber.

4. The highland barley fiber ecological concrete performance testing method according to claim 3 is characterized in that: The specific process of step (4) is as follows: A) Take out the concrete test block cured in the curing room and observe the regularity of its surface. Then soak the concrete test block in room temperature water for at least 4 days and then take it out. After wiping off the residual water on the surface of the concrete test block, weigh the mass of the concrete to obtain the initial mass of the concrete. B) First, set the freeze-thaw box control panel, set the temperature between -15℃ and -20℃, and the temperature should always be controlled within the range of no more than 15℃, set three freeze-thaw cycle gradients, 20 times, 40 times, and 50 times respectively; according to the different content of highland barley fiber, add 1Kg / m 3 , 2Kg / m 3 , 3Kg / m 3 , 4Kg / m 3 , 5Kg / m 3 Five groups of highland barley fiber concrete test blocks with different dosages were placed in a freeze-thaw box; C) When the test reaches 20 freeze-thaw cycles, stop the freeze-thaw box and wait for the concrete test blocks to be completely thawed. Then take out one-third of the concrete test blocks, weigh the mass of the concrete test blocks, and then measure the compressive strength of the concrete test blocks. After the test is completed, set 20 cycles to continue running the freeze-thaw box. After the operation is completed, take out the required concrete test blocks, weigh them and measure their compressive strength, and then continue to set 10 cycles. After the cycle is completed, measure the weight and compressive strength; if the mass of the concrete test block is reduced to less than 95% of the original after a certain cycle, or the compressive strength is reduced to less than 75% of the original, the concrete test block is considered to be damaged, the experiment is over, and the concrete anti-freeze grade is recorded as D + the number of freeze-thaw cycles.

5. The highland barley fiber ecological concrete performance testing method according to claim 4 is characterized in that: Step (5) includes antifreeze data processing, appearance analysis, mass loss rate analysis and compressive strength loss rate analysis.